The oncometabolite R-2-hydroxyglutarate inhibits microglial activation via the FTO/NF-κB pathway - Wang, Lu; Zhang, Huiting; Jing, Xifeng; Huang, Yuanchi; Kang, Yuxin; Qian, Yulan; Chen, Dong (Frontiers in Oncology, 2025)
IntroductionMutations in isocitrate dehydrogenase 1 (mIDH1) generate the oncometabolite (R)-2-hydroxyglutarate (R-2HG), which promotes tumorigenesis by inhibiting α-ketoglutarate-dependent enzymes and altering the epigenetic landscape. Microglia, the resident brain macrophages, are a key immune population in gliomas. While R-2HG is known to impair CD8+ T-cell function, its specific impact on microglial activation remains unknown. This study aimed to investigate the effect of R-2HG on microglial inflammatory responses.MethodsThe murine microglial BV2 cell line was stimulated with glioma-conditioned medium (CM) in the presence or absence of R-2HG. Cytokine production was analyzed, with a specific focus on IL-6. Mechanistic studies involved assessing the phosphorylation and nuclear translocation of key NF-κB pathway components (IκBα and p65). The dependency on α-ketoglutarate was tested via metabolite supplementation, and the role of the demethylase FTO was investigated.ResultsTreatment with glioma CM significantly induced cytokine production in BV2 cells. R-2HG specifically inhibited the activation of IL-6. Mechanistically, R-2HG suppressed CM-induced phosphorylation of IκBα and p65, thereby impairing the nuclear translocation of p65. The inhibitory effect of R-2HG on IL-6 was abolished by the addition of α-ketoglutarate. Further analysis demonstrated that R-2HG downregulates IL-6 expression by inhibiting the activity of the RNA demethylase FTO.DiscussionOur findings reveal that R-2HG specifically inhibits microglial inflammatory activation by suppressing the FTO/NF-κB signaling pathway, leading to decreased IL-6 production. This study provides a novel mechanism by which R-2HG modulates the tumor immune microenvironment, which may be beneficial for exploring the basis of antitumor immunity in IDH-mutant gliomas.